Evaluasi Kelayakan dan Faktor Penggunaan Jembatan Penyeberangan Orang (JPO) - Mone, Stefanus Gabriel; Seran, Engelbertha Noviani Bria; Pedo, Krisantus Satrio Wibowo (Local Engineering, 2024)
The availability of pedestrian bridge facilities is very necessary for the safety of pedestrian crossings in minimizing the risk of accidents. One of the pedestrian bridge facilities in Kupang City is on Jl. Ahmad Yani District. Old town. The level of feasibility and use of this footbridge is considered inadequate so it is necessary to evaluate the feasibility and factors of use of this footbridge. The method used is the method for determining crossing facilities according to Bina Marga standards to determine the suitability of pedestrian bridge facilities and the AHP method for determining factors in the use of pedestrian bridge. The results of the pedestrian bridge’s feasibility analysis show that the facilities required according to the calculation results are a zebra crossing with school safety zone (ZoSS) equipment, whereas based on a geometric review of the pedestrian bridge the safety and comfort aspects do not meet the requirements. The results of the analysis of respondents' answers regarding factors in using pedestrian bridge showed that 89% of respondents used pedestrian bridge for trial and error reasons and 50% of respondents answered that they did not use pedestrian bridge s because of construction constraints. Using AHP analysis, the factor that most influences the use of footbridges is the comfort factor (distance from the center of activity) with a distribution weight of 50%, followed by the comfort factor (lighting) with a distribution weight of 32%, then the safety factor (roof availability) with a distribution weight of 12% and finally the safety factor (bridge construction) with a distribution weight of 6%.